Comparative Analysis of Islamic and Conventional Banks Performance Using Sharia Maqasid Index and CAMEL - Rismayani, Gista; Nanda, Ulfa Luthfia (Universitas Islam Indonesia, 2019)
This research was conducted by analyzing the performance of Islamic banking and conventional banking using the sharia maqasid index approach and the CAMEL approach and comparing them. The data source used in this research is the audited and published annual reports from each of the bank websites that will be studied. In addition, other data sources used were obtained through Islamic banking statistics, articles, Bank Indonesia statistics, and others related to research. The results showed that there were significant differences in the performance of Islamic maqasid, the ratio of CAR, NPL, ROA, and FDR of Islamic Commercial Banks to Conventional Banks. The results of further research reject the hypothesis that there is no significant difference in the ratio of NPM and BOPO of Islamic Commercial Banks to Conventional Banks.